Arty Crafts - Cunanan,Laiza Lagrimas,Jenelyn Laxamana,Geraldine Mendoza,Eden Misamis,Mercedita Mojica,Darwin John Navarro,April Cita Salandanan,Carmela Joice and Vicente ,Paula Jean. 4 0 16; 5
u
Strategic Marketing Plan (BSBA major in Marketing) Pamantasan ng Lungsod ng Maynila 2008.
Keywords: 2 -- 0; 6; 20; 20; 2